2018
DOI: 10.1177/1071100718768020
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Medial Cuneiform Osteotomy to Correction of Longitudinal Arch Collapse in Stage IIb Adult-Acquired Flatfoot Deformity

Abstract: Level IV, Retrospective Case Series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 12 publications
(48 reference statements)
0
26
0
Order By: Relevance
“…They demonstrated that Cotton osteotomy graft size was the most significant predictor of change in the CAA and found that the size of the graft results in a linear change in the CAA. 12 For each millimeter increase in the graft size, there was a corresponding decrease in the CAA by 2.1 degrees. 12 Castaneda et al 2 and Kunas et al 12 reported average preoperative CAA to be 1.0 degrees and 1.3 degrees, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…They demonstrated that Cotton osteotomy graft size was the most significant predictor of change in the CAA and found that the size of the graft results in a linear change in the CAA. 12 For each millimeter increase in the graft size, there was a corresponding decrease in the CAA by 2.1 degrees. 12 Castaneda et al 2 and Kunas et al 12 reported average preoperative CAA to be 1.0 degrees and 1.3 degrees, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Kunas et al 12 used multivariable regression analysis to identify factors that significantly affected the CAA. They demonstrated that Cotton osteotomy graft size was the most significant predictor of change in the CAA and found that the size of the graft results in a linear change in the CAA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this is a relatively small case series, and an increased number of patients would further validate the results; on the other hand, the group size in the current study is similar to that in prior reports on metallic wedge implant utilization in the foot. 3,9…”
Section: Discussionmentioning
confidence: 99%
“…123 Although graft size was traditionally determined by intraoperative clinical judgment, there is interest in using linear-based equations to dictate graft size based on radiographic parameters. 76…”
Section: Forefoot Supinationmentioning
confidence: 99%